2021
DOI: 10.1007/s12144-021-01665-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social problem skills on academic motivation by means of Covid-19 fear

Abstract: Recent studies have investigated the relationship between the social problem-solving skills and academic motivation; nevertheless, new studies should examine the relationships between the social problem solving and academic motivation taking the effect of Covid-19 fear into consideration. As a result of this, in this study, it was aimed to a construct structural equation model by which the impacts of social problem-solving skills on academic motivation by means of Covid-19 fear were studied. Therefore, 513 uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
2
4
0
4
Order By: Relevance
“…A decrease in the motivational component of academic adaptation indicates a shift in emphasis from the academic process and results in more relevant processes related to physical health and its protection. These data are consistent with the results of studies that have established significant changes in subjective well-being and discomfort and a decrease in students' motivation due to the onset of the pandemic [59,60].…”
Section: Discussionsupporting
confidence: 91%
“…A decrease in the motivational component of academic adaptation indicates a shift in emphasis from the academic process and results in more relevant processes related to physical health and its protection. These data are consistent with the results of studies that have established significant changes in subjective well-being and discomfort and a decrease in students' motivation due to the onset of the pandemic [59,60].…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Günaydın HD. [67] analysed the impact of the ability to solve social problems on academic motivation by means of the fear of COVID-19. It was found that a positive orientation was regarded as a significant psychological source of strength to protect oneself against COVID-19-related mental issues.…”
Section: Discussionmentioning
confidence: 99%
“…Yeni öğrenmeler elde etmek, bu yolda emek sarfetmek ve bu yönde tutum ve davranıĢlar geliĢtirmek olarak görülebilecek akademik motivasyon, öğrenim sürecinde yer alan öğrenciler için gerçekleĢtirdikleri çalıĢmaları baĢarıyla sürdürmelerine ve performans göstermelerine olanak verecektir. Yeni öğrenmeler noktasında bireyin güdülenmesi olarak görülebilecek olan akademik motivasyon, bu durum için tutarlılık ve süreklilik de içermektedir (Günaydın, 2021).…”
Section: Gġrġġunclassified